Pengaruh Opportunity Growth, Gender Dewan Direksi, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Anthony Estevan (Journal of Business and Economics (JBE) UPI YPTK, 2019)
This study aims to determine the effect of opportunity growth, gender of the board of directors, and firm size on firm value with profitability as a control variable for manufacturing companies on the Indonesia Stock Exchange in the 2015-2019 period. The sampling technique was chosen by purposive sampling. The company sample consists of 42 companies listed in manufacturing companies listed on the Indonesia Stock Exchange with a research period of 5 years, namely 2015-2019. Financial report data was obtained from the Indonesia Stock Exchange (IDX) and the company's website (www.idx.co.id). The results of this study indicate that Opportunity Growth has a significant positive effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange. The gender of the Board of Directors has a significant negative effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange. Firm size has a significant negative effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange. Profitability has a significant positive effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange